Ciclo biologico del acaro carmin Tetranychus cinnabarinus, Acari: Tetranychus - Rodriguez M, N.
(Es, En)
Ilus., 8 ref.
Keywords: TETRANYCHUS CINNABARINUS; ACARINA; TETRANYCHIDAE; CICLO VITAL; CICLO BIOLOGICO; CUBA; ACARO CARMIN